Group Exhibition-Biennale of Young Artists of Europe and the Mediterranean, The Six Workshops in Sarajevo Project, Roma - Antoniou, Klitsa (My University, 2026)
Biennale of Young Artists of Europe and the Mediterranean, The Six Workshops in Sarajevo Project, Roma, Italy